Proprietary interests in commercial transactions - Worthington, Sarah 1955- (Clarendon Press, 1996)
This book provides an analysis and overview of personal property in a commercial context. Two features of the analysis are significant. The first is the unavoidable integration of contract and property law. Although proprietary interests may be broadly classified as ownership or security interests, these are relative concepts which are frequently subject to impinging contractual arrangements. The second is the prevalence of equitable proprietary interests. This prevalence is directly related to the ease with which equity is able to convert personal obligations into proprietary remedies. Sarah Worthington analyses these relationships and defines clear rules which better describe the incidence of proprietary interests. This is an important work in an area of immense commercial importance.
Keywords: Eigendom; Equity; Goederenrecht; Intérêt (Droit); Propriété mobilière; Sûretés (Droit); Vente - Droit; Interest (Ownership rights); Personal property; Sales; Security (Law); Eigentum; Handel